The relationship between the latency period, infection markers, and oxidant and antioxidant states in women with preterm premature rupture of membranes - Ilhan, N.; Aygun, B. K.; Gungor, H. (Springer London Ltd, 2017)
A major cause of perinatal morbidity and mortality has been reported to be preterm premature rupture of membranes (PPROM). Our objective was to evaluate oxidant-antioxidant balance, infection parameters, time interval between rupture of membranes and delivery (latency period), and the relationship among all these parameters. Seventy-five cases with PPROM between 24 and 34 gestational weeks were included in the study. A control group of 41 women who gave birth at term were considered as the control group. The relationship among maternal plasma total oxidative stress (TOS), malondialdehyde (MDA), total antioxidant status (TAS), leukocyte counts, CRP, vitamin C and E levels, gestational week, neonatal birthweight, and latency period was evaluated. In cases with PPROM, rupture occurred at an average of 29.4 gestational weeks and premature babies were born at an average of 31.6 gestational weeks. The mortality rate of babies born to PPROM women was 18.7% (14/75) died at or following birth. In the PPROM group, TOS, MDA, and leukocyte counts were found to be significantly higher compared to the control group (p < 0.001). Besides, a significant negative correlation was detected among the latency period, TOS, CRP, and leukocyte counts (p < 0.05). Appropriate treatment protocols that strengthen antioxidant defense systems and taking into consideration the signs of infection can decrease the incidence of PPROM and/or mortality rates of babies born to PPROM women.
Keywords: PPROM; Latency period; Inflammatory marker; Oxidant and antioxidant states